Soil water content measurement using polymer optical fibre Bragg gratings. Issue 1 (15th January 2022) - Mehravar, Moura; Yang, Hanrui; Webb, David J; Zhang, Wei; Sestelani, Sina Fadaie; Chapman, David N
Abstract : Measuring soil water content is crucially important and can affect soil strength, which is a key parameter in the analysis, design and monitoring of geo-structures. In this study, an optical fibre Bragg grating sensor inscribed in polymer optical fibre was developed, and for the first time, its ability to measure soil water content was investigated. The sensitivity of the sensor to different values of gravimetric soil water content under the different compaction conditions of loose and normal compaction was tested. The effect of soil temperature on the sensor's performance was considered. To assess the sensor's implementation, accuracy and reliability, a commercial soil water content probe (SM150), which measures volumetric soil water content was employed. The results indicate that the developed sensor, when calibrated correctly, is able to provide detailed data on any minor variation of soil water content (e.g. 0.5%) with high precision. The outcomes of this study define an additional capability of the polymer optical fibre Bragg grating sensors, which is significantly important for the long-term performance monitoring of geo-structures.